PERSPEKTIF HUKUM PIDANA ISLAM DAN HUKUM PIDANA POSITIF INDONESIA TERHADAP ANAK YANG MELAKUKAN KEJAHATAN - rahmad alamsyah (Menara Ilmu, 2020)
Abstract : The factors that cause children to commit delinquency consist of two kinds, namely intrinsic and extrinsic motivation. Intrinsic motivation is encouragement or desire in someone who does not need to be accompanied by stimulants from the outside. Extrinsic motivation is an impulse that comes from outside a person. The punishment for the crime of minors from the perspective of Islamic criminal law and positive criminal law is as follows: Based on Law Number 11 of 2012 concerning the Child Criminal Justice System, which came into force in 2014, it is known that "Children who are not yet 14 (fourteen) years can only be subject to action ". Based on this, the age limit for children who can be convicted or can be punished if interpreted, is almost in accordance with the concept of balig or adult concept in Islamic law, which is only fifteen years old; semen out; dreams of intercourse; start menstruating for women. Keywords: Islamic Criminal Law and Indonesian Positive Criminal Law, Child Delinquency, Crime against Children.